Confirmatory and validation studies on experimental self-efficacy scale with applications to multiple scientific disciplines - Kolil, Vysakh Kani; Parvathy, S. U.; Achuthan, Krishnashree (Frontiers in Psychology, 2023)
Laboratory education is essential for enhancing both the understanding of concepts and skills of students. A significant barrier to excelling in laboratory practices relates to a lack of self-efficacy. Being complementary to mainstream theoretical learning, the contribution of laboratory education to impart knowledge and hands-on proficiency is often under-represented. The aim of this research was to validate a novel experimental self-efficacy (ESE) scale and explore its relationship with laboratory outcomes, using gender and year of study as mediating variables. ESE refers to students' faith in their potential to carry out experiments and achieve desired outcomes in laboratory settings. When students possess strong ESE, they display more confidence in their abilities, accept tasks of greater difficulty levels, and have more tenacity to overcome obstacles. Data from 1,123 students were analyzed, focusing on the link between ESE constructs and laboratory experiments. Results indicated that ESE had a significant impact on laboratory performance in students of both genders and was related to factors such as laboratory hazards, conceptual understanding, the sufficiency of laboratory resources, and procedural complexities. The study affirms the validity and applicability of the ESE-scale to not only multiple disciplines such as chemistry, physics, and biology but also its relationship with students' academic outcomes in laboratories.